Tuning the luminescence performance of metal–organic frameworks based on d10 metal ions: from an inherent versatile behaviour to their response to external stimuli. Issue 44 (7th October 2016) - Cepeda, Javier; Rodríguez-Diéguez, Antonio
Abstract : An overview of tuning luminescent emission of Zn/Cd-MOFs through two approaches: inherent structural features and interplay with external species. Abstract : Metal–organic frameworks (MOFs) are an interesting class of porous crystalline solids assembled from organic ligands and metal clusters (or simply metal cations), which have shown a rich variety of promising applications. In recent years, these interesting materials have become one of the most actively studied areas in the field of new materials development. One of the most interesting aspects of MOFs is their optical properties and porosity, which may be smartly coupled with the aim of creating multifunctional materials. This work gives an overview of the most significant achievements on this particular theme by bringing an up-to-date collection of work focused on tuning the luminescent emission of MOFs, according to structural changes derived from their porous nature.